Analisis Isi Sinetron Cinta Setelah Cinta di Sctv Dalam Perspektif Gender - Firdaus , Ilyas; Manalullaili; Muslimin (CV. ITTC INDONESIA, 2023)
In this research the researcher will use a critical paradigm. The critical paradigm seeks to combine theory and action (praxis) consciously.